Relationship between cyanogenic compounds in seeds, leaves and roots of sweet and bitter kernelled almonds - Dicenta F.; Martínez-Gómez P.; Berenguer V.; Grané N.; Martín M.L.; León A. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
The relationship between the resistance to capnode (Capnodis tenebrionis L.) in almond (Prunus dulcis Miller) and the presence of some cyanogenic compounds in roots has been pointed out. However, some aspects such as the relationship between the content of cyanogenic compounds in the different parts of the plant remain unclear. In this work the content of these compounds in kernels, leaves and roots of 5 sweet kernelled, 5 slight bitter kernelled and 5 bitter kernelled almond trees was determined. The results show a good correspondence between the content of cyanogenic compounds in kernels and roots. Given that inheritance of kernel bitterness is known to be a monogenic trait, these results open new possibilities for the breeding of new cultivars with a high content of cyanogenic compounds in roots, probably resistant to capnode.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)